Oblivions of New York. Temporality and memory it the heterotopic spaces of the urban fabric - Fernández Posadas, Javier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2024)
Throughout the 19th century, the Commissioners’ Plan of 1811 and the emerging forces of modernity established the groundwork for what could be termed the "permanent temporality" of New York City, positioning it as an ideal setting for exploring the relationship between memory and space. This quality, which places change and the “culture of congestion” as constants of the metropolis’s urban fabric, provides lessons for the development of cities in the 21st century. Through Michel Foucault’s concept of heterotopia, we can understand urban areas not only as scenes of physical and temporal transformations but as assemblies of “other spaces” that exist in parallel, challenging and complementing narratives of permanence over time. Following also the urban theories of Henri Lefebvre, Richard Sennett, Susan Fainstein, and Rem Koolhaas, this article examines the role of some heterotopic spaces in New York that, filled with layers and meanings, redefine our perception of stability and temporality in the urban context. The intersections between real and heterotopic space thus reveal “oblivions” surpassed by historical becoming, underlining the importance of considering these spaces to negotiate the role of memory in future urban planning and development.